Atlas of Retinal Detachment Diagnosis and Differential Diagnosis (Springer Singapore, 2018)
This atlas and textbook aims to provide diverse pictures, facilitating the readers to learn fundus diseases. Retinal detachment is a common group of vitreo-retinal diseases that causes blindness. The diagnosis and differential diagnosis are dependent mostly on ophthalmolscopy and fundus imaging technology. With the development of imaging technology, it is getting easier for ophthalmologist to make quick and accurate decision on the diagnosis. The book includes both common types of retinal detachment and some rare diseases. Moreover, some diseases without but related to retinal detachment are included in the book. In addition to traditional color fundus photos, fundus fluorescent angiography, ultrasound and traditional OCT images, OCT angiography and ultrasound angiography images are included too. This book also contains brief introductions to each disease. Differentiated from detailed review of pathogenesis or treatment, the readers will discover concise yet direct concept. This atlas and textbook is yours to read and enjoy, but also to use as a valuable tool in your management of the patient with retinal detachment. Keep it handy. We hope doctors in training and those who have had certain clinical experiences interested in vitro-retinal diseases can benefit from this book.